Bridging the smallholder finance gap: Collaborative research with WeGro in Bangladesh - Ambler, Kate; Bakhtiar, M. Mehrab; de Brauw, Alan; Uddin, Mohammad Riad (International Food Policy Research Institute, 2023)
Farmers in many low- and middle-income countries face a major financial gap, with available resources often insufficient to enable them to increase production—and putting many higher-value products with the greatest potential to increase incomes out of reach. Yet banks and other formal financial institutions shy away from lending to smallholder farmers.